Hardware acceleration of BWA-MEM genomic short read mapping for longer read lengths. (August 2018) - Houtgast, Ernst Joachim; Sima, Vlad-Mihai; Bertels, Koen; Al-Ars, Zaid
Abstract: We present our work on hardware accelerated genomics pipelines, using either FPGAs or GPUs to accelerate execution of BWA-MEM, a widely-used algorithm for genomic short read mapping. The mapping stage can take up to 40% of overall processing time for genomics pipelines. Our implementation offloads the Seed Extension function, one of the main BWA-MEM computational functions, onto an accelerator. Sequencers typically output reads with a length of 150 base pairs. However, read length is expected to increase in the near future. Here, we investigate the influence of read length on BWA-MEM performance using data sets with read length up to 400 base pairs, and introduce methods to ameliorate the impact of longer read length. For the industry-standard 150 base pair read length, our implementation achieves an up to two-fold increase in overall application-level performance for systems with at most twenty-two logical CPU cores. Longer read length requires commensurately bigger data structures, which directly impacts accelerator efficiency. The two-fold performance increase is sustained for read length of at most 250 base pairs. To improve performance, we perform a classification of the inefficiency of the underlying systolic array architecture. By eliminating idle regions as much as possible, efficiency is improved by up to +95%. Moreover, adaptive load balancing intelligently distributes work between host and accelerator to ensure use of an accelerator always results in performance improvement, which in GPU-constrained scenarios provides up to +45% more performance.